Major Domestication-Related Phenotypes in Indica Rice Are Due to Loss of miRNA-Mediated Laccase Silencing. Issue 11 (19th October 2018) - Swetha, Chenna; Basu, Debjani; Pachamuthu, Kannan; Tirumalai, Varsha; Nair, Ashwin; Prasad, Melvin; Shivaprasad, P. V.
Abstract : Altered lignification mediated by microRNA-directed laccase gene silencing is a major contributor to domestication-associated phenotypes of cultivated indica rice. Abstract: Domestication of rice ( Oryza sativa ) included conversion of perennial wild species with few seeds to short plants that produced abundant seeds. Most domestication-associated changes were due to variations in transcription factors and other key proteins such as enzymes. Here, we show that multiple yield-related traits associated with indica rice domestication are linked to micro (mi) RNA-mediated regulation. Analysis of small (s) RNA data sets from cultivated indica rice lines, a few landraces, and two wild relatives of rice revealed the presence of abundant 22-nucleotide (nt) reads in wild relatives that mapped to miR397 precursors. miR397 was expressed at very high levels in wild relatives and at negligible levels in high-yielding cultivated lines. In its genera-specific form of 22-nt, miR397 targeted mRNAs encoding laccases that decayed and induced robust secondary cascade silencing in wild species that required RNA-dependent RNA polymerase 6. In wild species of rice, reduced expression of laccases resulted in low lignification. As expected, overexpression of miR397 induced de-domestication phenotypes. At least 26 uncharacterized QTLs previously implicated in rice yield overlapped with laccases and miR397 genes. These results suggest that miRNAs contribute to rice domestication-associated phenotypes.